A study on the impact of digital financial inclusion on inclusive growth in China: The mediating effect of innovation - Wang, Qian; Yu, Han-Hsing (International Journal of Innovative Research and Scientific Studies, 2024)
This study empirically explores the impact, regional variations and transmission mechanisms of digital financial inclusion on inclusive growth. A provincial panel dataset encompassing 31 Chinese provinces from 2011 to 2021 was collected from the wind database, the China statistical yearbook and the China regional financial operation report to analyze the relationship between digital financial inclusion and inclusive growth by using individual fixed effects and mediating effects. This study reveals that digital financial inclusion significantly influences the growth of China’s east, central, west regions and economic growth, income distribution and opportunity equality. Moreover, digital financial inclusion can enhance inclusive growth through the transmission mechanism of innovation. Developing digital financial inclusion, comprising coverage breadth, usage depth and digital level will promote the level of inclusive growth in China. Meanwhile, the increasing level of innovation, especially the number of invention patents can support digital financial inclusion by fostering inclusive growth. The study focuses on Chinese provinces and reliance on a specific timeframe (from 2011 to 2021) might limit the generalizability of the findings. The implications for broader economic contexts need further exploration. Accelerating progress towards inclusive growth can be achieved by fostering the development of digital financial inclusion and elevating the level of innovation. This study contributes by highlighting the positive relationship between digital financial inclusion, regional disparities and its impact on inclusive growth, emphasizing the role of innovation in this relationship and suggesting policy directions for achieving inclusive growth.